Challenges for Policy mix in the Context of the Financial Crisis – the Case of Poland - Stawska, Joanna; Grzesiak, Lena (Journal of Finance and Financial Law, 2014)
The aim of this article is to present the essence of policy mix and the extraordinary actions undertaken by the monetary and fiscal authorities in Poland in response to the recent financial crisis. In the article, the hypothesis has been put forward that the challenges faced by monetary and fiscal authorities have contributed to carrying out coordinated actions, especially in support of economic growth during the recent financial crisis. As a result, in Poland during the last financial crisis, it seemed to observe greater cooperation between monetary and fiscal authorities.